Protective Effects of Phellinus linteus Mycelium on the Development of Osteoarthritis after Monosodium Iodoacetate Injection. (18th August 2020) - Shin, Mi-Rae; Lee, Jin A; Kim, Min Ju; Park, Hae-Jin; Park, Byeong Wook; Seo, Seung Bo; Roh, Seong-Soo
Abstract : Objective . The aim of this study was to identify the protective effects of Phellinus linteus mycelium (PLM) and its possible mechanisms in a model of monosodium iodoacetate- (MIA-) induced osteoarthritis (OA). Methods . Intra-articular injection of MIA was injected to 50 μ L with 80 mg/mL using a 0.3 mL insulin syringe into the right knee joint. Changes in hindpaw weight-bearing distribution between the right (osteoarthritic) and left (contralateral control) legs were used as an index of joint discomfort. PLM (50, 100, and 200 mg/kg body weight) was orally administered once daily for 14 days from day 7 after MIA treatment. And then, various factors associated with inflammatory response and cartilage degeneration in cartilage tissues detected by western blotting. Results . PLM treatment showed a concentration-dependent elevation in change in hindpaw weight-bearing distribution (HWBD). PLM200 demonstrated the capacity to significantly increase HWBD, indicating that the change in weight-bearing distribution means the reduction of spontaneous pain. Our results indicate that PLM suppressed the inflammatory factors via NF- κ B signaling pathway induced by p38 phosporlyation. Moreover, PLM200 exhibited a significant reduction of ROS produced by the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. PLM100 and PLM200 inhibited the levels of matrix metalloproteinase (MMP)-1, one of proteinase that degrades extracellular matrix (ECM). Conclusions . Taken together, our results indicated that PLM has a strong chondroprotective effect through the suppression both ROS production and inflammation.